Malignant Transformation of Mature Cystic Teratoma Diagnosed after a 10-Year Interval - Mariko Jitsumori; Satoru Munakata; Toshiya Yamamoto (Case Reports in Obstetrics and Gynecology)
A 67-year-old uniparous woman had undergone surgery for acute perforated gastric ulcer 10 years prior to the current presentation. Although abdominal computed tomography (CT) performed at that point had revealed a mature cystic teratoma measuring 6 cm in diameter in the right ovary, it was left untreated. She visited the department of surgery at our hospital with chief complaints of appetite loss, nausea, and vomiting that had persisted for the prior two weeks. She was admitted with a diagnosis of ileus attributed to an abdominal incisional hernia. CT performed on admission revealed a tumor measuring 21 cm in diameter with mural nodules in the right ovary. Thus, surgery was performed under suspicion of malignant transformation of the previously detected ovarian mature cystic teratoma. While neither lymphadenopathy nor distant metastasis was detected by imaging studies, bilateral adnexectomy and repair of the abdominal incisional hernia were performed. Cytology of ascites was negative. The postoperative pathological diagnosis was squamous cell carcinoma arising from teratoma, and the postoperative clinical diagnosis was stage IA ovarian cancer. It was assumed that the mature cystic teratoma which had been detected in the right ovary 10 years earlier had undergone malignant transformation.